Implementing Fuzzy Spelling Search in Dictionaries of Under-Described Languages Lacking Standard Orthographies (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2024)
Non-standard orthographies are common in the world of under-described language documentation. Whether they are semi-conventionalised community spellings, orthographies partially adopted from missionary works, or hastily transcribed texts representing as-yet uncertain phonologies, there is a need to be able to work through lexical data in a way which can accommodate and respond to such non-standard transcriptions. Here, a few options are considered, with a solution for fuzzy string matching based on attested variations is presented.